Pengaruh Pengendalian Internal dan Kompensasi terhadap Fraud di PT Mega Finance Tanjungsari - Doni Reynaldi; Badriyatul Huda; Armansyah M. Sarusu (Jurnal Dimamu, 2022)
Based on the results of interviews with the Admin Head and Sales Coordinator, the lack of compensation and internal control is the cause of fraud, this is evidenced by data for the last 5 years the number of customers and the number of employees at PT Mega Finance Tanjungsari which has fluctuated. This study was conducted to determine how the influence of internal control on fraud, the influence, the effect of compensation on fraud and the influence of internal control and compensation simultaneously on fraud. The object of research that is the target of research is employees at PT Mega Finance Tanjungsari with associative quantitative research, while the data needed is data taken directly to the field or called primary data. In the sampling, 21 employees at PT Mega Finance Tanjungsari were taken in 2020. The results showed that there was an influence between internal control on fraud with the results of the t test 2.620 < t table 2.093. And there is a significant effect between compensation for fraud with the results of the t-test tcount 4,942 > ttable 2,093. Meanwhile, simultaneously there is a significant influence between internal control and compensation for fraud with the results of the F test where the value of Fcount is 14.7 > Ftable 3.52.